The effect of uranyl acetate toxicity in the tissues of the heart, Liver, kidney and blood physiological & biochemical Parameters in male rabbit’s - AL-Hamzawy, Nael M. S. (Al-Qadisiyah Journal of Pure Science, 2017)
The aim of current research to study changes in some tissues and physiological and biochemical blood tests resulting from the effect of the uranyl acetate toxicity with using concentrations (25,35) mgrepresent in high rates as one of the salts of uranium, spreading in some endemic areas with this toxic and radioactive substance. The study included 18 animals of local’s rabbits ,which were divided into three groups, the control group: that was treated orally 1 ml kg of Physiological salt solution (Normal Saline) during the trial period amounting one month (30 days),The first group: treated 25 mg kg of body weight of the animal the length of the experiment, The second group was treated 35mg kg of body weight during the experiment. The results of the experiment Showed that there was a significant decrease (P <0.05) in red blood corpuscles count (RBCc) and Packed cells volume (PCV), while there was a significant increase in both the amount of Hemoglobin (Hb) and white blood cells count (WBCc) in comparison with control group. As for the results of biochemical blood tests have revealed the existence of a significant increase (P <0.05) in the amount of triglycerides( TG), cholesterol (S.Chol), urea (Urea), creatinine (Creat.) in the blood, also appeared significant increase in the proportion of functions enzymes of the liver (ALT, AST) and the amount of sugar(Glucose) in the blood of animals in the two treatments groups, while there was a significant decrease (P <0.05) in the amount of total protein (T.Protein) in the blood of treated animals when compared to the control group of the two groups also. The microscopic examination of sections showed cardiac muscle tissue an dilation and flayed in the lining of the blood vessel and the relapse of the nuclei of cells with the appearance of die cellular lysis of the parts of cells, as shown in the second group changes the biggest was the appearance of large hemorrhage to red blood cells (RBC) in the blood vessel and spread of these corpuscles between the cells with a total damage of the tissue. The histological sections of liver showed revealing narrowing of the central vein, bleeding of erythrocytes (RBCs), damage to cell membranes and conglomerate nuclei, with the large congestion in central vein with RBC and the cells die and the appearance of inflammatory cells (Pus Cells). While the sections of kidney showed conglomerate in glomerulus and flayed the lining of Bowman’s capsule with the expansion of tubular tract and found to dead cells, In an increase of the concentration of acetate has been damaged completely fitting histological kidney with stenosis significantly proximal tubule and expansion in the blood vessel and the emergence of erythrocytes (RBC) and inflammatory cells (Pus Cells). It can be concluded that the entry of high concentrations of uranium or one of its salts to the body or even exposure in endemic areas to this substance lead to healthy effects and significant side can be considered very dangerous to the life of the organism marked by changes in the structures and functions of the body organs, which indicated the healthy ills cases that led to it the high concentrations used in the experiment after exposure of animals, so it must caution strongly of the seriousness of this substance.